Results of the Response of State Defense and Scout Activities (Vocational High School Studies and the Equivalent in Blitar Raya) - Muhammad Iqbal Baihaqi; Ida Putri Rarasati (JOSAR (Journal of Students Academic Research), 2021)
In reality in everyday life, students today are students who are more skilled in operating information technology. Apart from being supported by their expertise, the existing facilities are also very influential. Therefore, many abuses have resulted in negative influences such as drug use, indifference, and even insecurity about themselves and their country. This incident cannot be ignored, young people are the next generation of the nation who should protect and defend the unitary Republic of Indonesia. Therefore, the government should form a curriculum that implements character education and State defense with the aim of fostering a love for the nation itself. The results of this study are in the form of national defense and scouting education which is expected to increase awareness of love for the country and the nation as well as character education for students, especially high school students and the equivalent. Based on the results of the study, it can be seen that the holding of scouting activities at high school level has a good influence on student personality. This can be seen from the abilities and skills of students in thinking and being able to apply good behavior in everyday life.